Effects of pulse duration on magnetostimulation thresholds - Saritas, Emine U.; Goodwill, Patrick W.; Conolly, Steven M. (Medical physics (Lancaster), 2015)
Purpose: Medical imaging techniques such as magnetic resonance imaging and magnetic particle imaging (MPI) utilize time‐varying magnetic fields that are subject to magnetostimulation limits, which often limit the speed of the imaging process. Various human‐subject experiments have studied the amplitude and frequency dependence of these thresholds for gradient or homogeneous magnetic fields. Another contributing factor was shown to be number of cycles in a magnetic pulse, where the thresholds decreased with longer pulses. The latter result was demonstrated on two subjects only, at a single frequency of 1.27 kHz. Hence, whether the observed effect was due to the number of cycles or due to the pulse duration was not specified. In addition, a gradient‐type field was utilized; hence, whether the same phenomenon applies to homogeneous magnetic fields remained unknown. Here, the authors investigate the pulse duration dependence of magnetostimulation limits for a 20‐fold range of frequencies using homogeneous magnetic fields, such as the ones used for the drive field in MPI. Methods: Magnetostimulation thresholds were measured in the arms of six healthy subjects (age: 27 ± 5 yr). Each experiment comprised testing the thresholds at eight different pulse durations between 2 and 125 ms at a single frequency, which took approximately 30–40 min/subject. A total of 34 experiments were performed at three different frequencies: 1.2, 5.7, and 25.5 kHz. A solenoid coil providing homogeneous magnetic field was used to induce stimulation, and the field amplitude was measured in real time. A pre‐emphasis based pulse shaping method was employed to accurately control the pulse durations. Subjects reported stimulation via a mouse click whenever they felt a twitching/tingling sensation. A sigmoid function was fitted to the subject responses to find the threshold at a specific frequency and duration, and the whole procedure was repeated at all relevant frequencies and pulse durations. Results: The magnetostimulation limits decreased with increasing pulse duration (Tpulse). For Tpulse < 18 ms, the thresholds were significantly higher than at the longest pulse durations (p < 0.01, paired Wilcoxon signed‐rank test). The normalized magnetostimulation threshold (BNorm) vs duration curve at all three frequencies agreed almost identically, indicating that the observed effect is independent of the operating frequency. At the shortest pulse duration (Tpulse ≈ 2 ms), the thresholds were approximately 24% higher than at the asymptotes. The thresholds decreased to within 4% of their asymptotic values for Tpulse > 20 ms. These trends were well characterized (R2 = 0.78) by a stretched exponential function given by BNorm=1+αe−Tpulse/βγ, where the fitted parameters were α = 0.44, β = 4.32, and γ = 0.60. Conclusions: This work shows for the first time that the magnetostimulation thresholds decrease with increasing pulse duration, and that this effect is independent of the operating frequency. Normalized threshold vs duration trends are almost identical for a 20‐fold range of frequencies: the thresholds are significantly higher at short pulse durations and settle to within 4% of their asymptotic values for durations longer than 20 ms. These results emphasize the importance of matching the human‐subject experiments to the imaging conditions of a particular setup. Knowing the dependence of the safety limits to all contributing factors is critical for increasing the time‐efficiency of imaging systems that utilize time‐varying magnetic fields.